Determinant of Early Complementary Feeding Practices ind Karanganyar Sub-District Surakarta - Wuryaningsih, Emi Wuri (Jurnal Keperawatan Soedirman, 2009)
Early complementary feeding practices on infant and baby still often founded in society living before fourth months. Early complementary feeding practices is one of the potential factors increasing infants morbidity because of it the infants more easily get Acute Respiratory Infection (ARI), diarrhea, allergies, and negative effect to nutrition status. This study is to Identify the factors Influencing early complementary feeding practices in urban area Jumantono Subdistrict Karanganyar District Surakarta Central Java.The design of study was cross sectional where the data was processed by descriptive and analytic ways with quantitative methods. The study was conducted in Jumantono of Karanganyar District, Surakarta Central Java and was done on may 2007. The population of this study were mothers who have baby between 0-6 months. The sampling is 105 mothers who were selected using the cluster random sampling and purposive sampling. In this study, the questionnaire was developed by the investigators from a review of the literature. The result data was analyzed by frequency distribution and chi square test.The study showed that 70,5% babies receiving early complementary food and most of them given on 1-<2 months of age. There was 24,8% of 32,4% of babies receiving complementary feeding in first 2 months of age. The result of bivariate analysis showed that between education, job, ANC frequencies, frequency for coming to professional healthy center, perception of mother about early complementary feeding, on one side, and early complementary feeding, on the other side, statistically was insignificant (p>0,05). On the other hand, the association between information resources of mother about infant and baby feeding, statistically was significant p=0,001 (p<0,05).Ã‚Â Information resources of mother about impact of early complementary feeding and exsclusive breastfeeding influencing mothers to give early complementary feeding. Mother who have information sources from non health providers tend to give complementary food more early of age babies compared to from health care providers. Midwives and nurses can encourage exclusive breastfeeding and complementary feeding to mother through ANC program and Pos Pelayanan Terpadu (Posyandu)